Changes in Cognitive Performance With Age in Adults With Multiple Sclerosis. Issue 3 (September 2019) - Baird, Jessica F.; Cederberg, Katie L.J.; Sikes, E. Morghen; Jeng, Brenda; Sasaki, Jeffer E.; Sandroff, Brian M.; Motl, Robert W.
Abstract : Background: Cognitive impairment is one of the most common consequences of multiple sclerosis (MS), yet there is a shortage of data regarding how cognition changes during the life span of individuals with MS. This information is of increasing importance given the growing proportion of older adults with MS. Objective: To study possible changes in cognitive function in correlation with increasing age in individuals with MS. Methods: Participants (N=129) were recruited and a priori allocated into one of three age groups (young, middle-aged, and older). All participants completed the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) during a single laboratory testing session. The BICAMS measures cognitive processing speed as well as verbal and visuospatial learning and memory. Results: A multivariate analysis of variance indicated that cognitive function significantly differed by age group, and these differences were not explained by amount of physical activity, years of education, years since diagnosis, or race. Older adults displayed significantly worse cognitive processing speed than young and middle-aged adults. The older and middle-aged adults also demonstrated significantly worse visuospatial learning and memory than the younger adults. Effect sizes indicated that cognitive processing speed and verbal learning and memory were more affected in late adulthood than early adulthood, whereas visuospatial learning and memory was affected similarly in early and late adulthood. Conclusions: Older adults with MS demonstrated significant impairments in cognitive function compared to young and middle-aged adults with MS. Future studies should determine the predictors of cognitive decline in this age cohort.